The Effect of Motivation, Working Environment and Compensation on Employee Performance through Work Satisfaction as Intervening Variable: The Case of PT. Sari Rasa OKI Regency - Dirgantara, Evan; Fatimah, Fatimah; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to determine the Effect of Work Motivation, Work Environment, and Compensation on Employee Performance Through Job Satisfaction as an Intervening Variable at PT Sari Rasa, OKI Regency. This research is associative. The variables used by researchers include Work Motivation, Work Environment, Compensation, Job Satisfaction, and Performance. The population of this study comprises all employees of PT Sari Rasa, totaling 165, and the sample consisted of 150; the sampling technique used was simple random sampling. The data used in this study are primary, collected through a questionnaire. The data analysis technique used is Structural Equation Modeling (SEM) with the LISREL program. The results of this study indicate that: 1) Work motivation has a significant effect on the job satisfaction of PT Sari Rasa, OKI Regency. 2) The work environment has no significant effect on the job satisfaction of PT Sari Rasa, OKI Regency. 3) Compensation has a significant effect on the job satisfaction of PT Sari Rasa, OKI Regency. 4) Work motivation has a significant effect on employee performance at PT Sari Rasa, OKI Regency. 5) The work environment has a significant effect on employee performance at PT Sari Rasa, OKI Regency. 6) Compensation has a significant effect on employee performance at PT Sari Rasa, OKI Regency. 7) Job satisfaction has a significant effect on employee performance at PT Sari Rasa, OKI Regency. Job satisfaction strengthens the influence of work motivation, the work environment, and compensation on employee performance at PT Sari Rasa in OKI Regency.